Determination of the functional elements within the vacuolar targeting signal of barley lectin. - Dombrowski, J E (1993)
We have previously demonstrated that the carboxyl-terminal propeptide of barley lectin is both necessary and sufficient for protein sorting to the plant vacuole. Specific mutations were constructed to determine which amino acid residues or secondary structural determinants of the carboxyl-terminal propeptide affect proper protein sorting. We have found that no consensus sequence or common structural determinants are required for proper sorting of barley lectin to the vacuole. However, our analysis demonstrated the importance of hydrophobic residues in vacuolar targeting. In addition, at least three exposed amino acid residues are necessary for efficient sorting. Sorting was disrupted by the addition of two glycine residues at the carboxyl-terminal end of the targeting signal or by the translocation of the glycan to the carboxy terminus of the propeptide. These results suggest that some components of the sorting apparatus interact with the carboxy terminus of the propeptide.